predictive value of the 70-gene signature for adjuvant chemotherapy in early breast cancer - Knauer, Michael; Mook, Stella; Rutgers, Emiel J. T; Bender, Richard A; Hauptmann, Michael; van de Vijver, Marc J; Koornstra, Rutger H. T; Bueno-de-Mesquita, Jolien M; Linn, Sabine C; van 't Veer, Laura J (Breast cancer research and treatment, 2010)
Multigene assays have been developed and validated to determine the prognosis of breast cancer. In this study, we assessed the additional predictive value of the 70-gene MammaPrint signature for chemotherapy (CT) benefit in addition to endocrine therapy (ET) from pooled study series. For 541 patients who received either ET (n = 315) or ET + CT (n = 226), breast cancer-specific survival (BCSS) and distant disease-free survival (DDFS) at 5 years were assessed separately for the 70-gene high and low risk groups. The 70-gene signature classified 252 patients (47%) as low risk and 289 (53%) as high risk. Within the 70-gene low risk group, BCSS was 97% for the ET group and 99% for the ET + CT group at 5 years with a non-significant univariate hazard ratio (HR) of 0.58 (95% CI 0.07-4.98; P = 0.62). In the 70-gene high risk group, BCSS was 81% (ET group) and 94% (ET + CT group) at 5 years with a significant HR of 0.21 (95% CI 0.07-0.59; P < 0.01). DDFS was 93% (ET) versus 99% (ET + CT), respectively, in the 70-gene low risk group, HR 0.26 (95% CI 0.03-2.02; P = 0.20). In the high risk group DDFS was 76 versus 88%, HR of 0.35 (95% CI 0.17-0.71; P < 0.01). Results were similar in multivariate analysis, showing significant survival benefit by adding CT in the 70-gene high risk group. A significant and clinically meaningful benefit was observed by adding chemotherapy to endocrine treatment in 70-gene high risk patients. This benefit was not significant in low risk patients, who were at such low risk for recurrence and cancer-related death, that adding CT does not appear to be clinically meaningful.